2011
DOI: 10.1136/jech.2011.142976l.61
|View full text |Cite
|
Sign up to set email alerts
|

P2-431 Marital status and risk of HIV infection in informal urban settlements of Nairobi, Kenya: results from a cross-sectional survey

Abstract: Conclusions Significant numbers of children have a low or critically decreased body fat mass. This problem is very vital and has to be evaluated as a highly dangerous risk factor for health and prospective life quality of the children. It is recommended to use FMI when analysing changes in body mass. Hyperdiagnosics of adiposity occurs when BMI is used. Introduction Case series suggest pregnant women are at increased risk of contracting H1N1 and experiencing complications. Published studies to date have invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
3
10
1
Order By: Relevance
“…And the HIV test yield significantly increased within each category of marital status, with the highest yield being among the divorced/separated individuals, followed closely by those widowed and maarried (table 2). This finding is similar to that of Legisso TZ and Erango Ma in Ethiopia where they found that divorced and married individuals were 3.033 and 1.031 times respectively, more likely to be HIV positive as compared to single individuals [8], and Kimani J et al in Kenya where they found that those who were divorced/separated/widowed were 4.06times and those married were 1.78 times more likely to be HIV positive than those never married [9]. Similar findings were observed by Adeniyi et al who identified being formerly married (divorced/separated/widowed) as a risk factor to HIV infection compared to being currently married or never married [10] and Adebayo SB et al who showed that HIV prevalence of women that were formerly married (divorced/separated/widowed) were more than double that of those who were currently married/cohabiting with a sexual partner; and more than three times those that were never married [11].…”
Section: Discussionsupporting
confidence: 84%
“…And the HIV test yield significantly increased within each category of marital status, with the highest yield being among the divorced/separated individuals, followed closely by those widowed and maarried (table 2). This finding is similar to that of Legisso TZ and Erango Ma in Ethiopia where they found that divorced and married individuals were 3.033 and 1.031 times respectively, more likely to be HIV positive as compared to single individuals [8], and Kimani J et al in Kenya where they found that those who were divorced/separated/widowed were 4.06times and those married were 1.78 times more likely to be HIV positive than those never married [9]. Similar findings were observed by Adeniyi et al who identified being formerly married (divorced/separated/widowed) as a risk factor to HIV infection compared to being currently married or never married [10] and Adebayo SB et al who showed that HIV prevalence of women that were formerly married (divorced/separated/widowed) were more than double that of those who were currently married/cohabiting with a sexual partner; and more than three times those that were never married [11].…”
Section: Discussionsupporting
confidence: 84%
“…This was statistically significant. This is surprising because it has been demonstrated that single people are more likely to contract HIV than married people [23]. However this may be because there are more female HIV positive patients in this study and married women in Nigeria have less bargaining power in sexual issues, hence are prone to contracting HIV.…”
Section: Discussioncontrasting
confidence: 46%
“…High rates of male infidelity in marriage have been found in Southern Africa, which can lead to high levels of sero-discordancy (Shandera, 2007; Chemaitelly et al, 2012; Dunkle et al, 2008; De Walque, 2007). Kimani and colleagues (2013) found that HIV prevalence was higher for married respondents than unmarried respondents in urban informal settlements in Kenya. Furthermore, HIV prevalence has been found higher for young married women compared to young unmarried women (Glynn et al, 2001; Kelly et al, 2003), which suggests that HIV could have been contracted during marriage.…”
Section: Introductionmentioning
confidence: 92%